The Influence of Competence, Religiosity, Ethical Climate, and Gender on Whistleblowing: A Study of Public Accounting Firms in Pekanbaru - Yolanda Arsita Putri (Asosiasi Dosen Akuntansi Indonesia, 2026)
This study aims to examine the effect of competence, religiosity, ethical climate, and gender on whistleblowing at Public Accounting Firms (KAP) in Pekanbaru. This research employs a quantitative survey method and multiple linear regression analysis. The results show that competence, religiosity, and ethical climate significantly affect whistleblowing, indicating that auditors with strong competence, religiosity, and ethical work environments are more likely to report wrongdoing. Meanwhile, gender has no significant effect on whistleblowing. This study is expected to contribute to the development of ethical work environments in Public Accounting Firms. Keywords: whistleblowing, competence, religiosity, ethical climate, gender.